PERAN MEDIASI KEBIJAKAN DIVIDEN PADA PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2022 - Soeparyanto, Wiwiek Wiyiastuty (JIM : Journal Of International Management, 2023)
This research aims to determine and analyze the mediating role of dividend policy on the influence of good corporate governance (independent board of commissioners, institutional ownership, managerial ownership) on the financial performance of banks listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period using a purposive sampling method with sample of 8 customers. The analysis technique used is multiple regretion linear analysis using path analysis. The results of this research indicate that Dividend Policy has no significant effect in mediating the Influence of the Independent Board of Commissioners and Managerial Ownership on the Financial Performance of Banks listed on the BEI for the 2018-2022 period; However, Institutional Ownership has a significant influence on Dividend Policy and Financial Performance of Banks listed on the IDX for the 2018-2022 period.